2014
DOI: 10.1039/c4lc00197d
|View full text |Cite
|
Sign up to set email alerts
|

Microdevice arrays of high aspect ratio poly(dimethylsiloxane) pillars for the investigation of multicellular tumour spheroid mechanical properties

Abstract: We report the design, fabrication and evaluation of an array of microdevices composed of high aspect ratio PDMS pillars, dedicated to the study of tumour spheroid mechanical properties. The principle of the microdevice is to confine a spheroid within a circle of micropillars acting as peripheral flexible force sensors. We present a technological process for fabricating high aspect ratio micropillars (300 μm high) with tunable feature dimensions (diameter and spacing) enabling production of flexible PDMS pillar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…PDMS micro-well arrays (see Supplementary Fig. S2) coated with Pluronic-F127 (Sigma, #P2443) to prevent cell adhesion 27 were fixed to the glass bottom of a Petri dish (FluoroDish WPI#50-823-005, Sarasota, USA) using an oxygen plasma torch (Elveflow, Paris, France). The Petri dish was then filled with 4 ml of culture medium before adding one spheroid in each micro-well using a micropipette.…”
Section: Methodsmentioning
confidence: 99%
“…PDMS micro-well arrays (see Supplementary Fig. S2) coated with Pluronic-F127 (Sigma, #P2443) to prevent cell adhesion 27 were fixed to the glass bottom of a Petri dish (FluoroDish WPI#50-823-005, Sarasota, USA) using an oxygen plasma torch (Elveflow, Paris, France). The Petri dish was then filled with 4 ml of culture medium before adding one spheroid in each micro-well using a micropipette.…”
Section: Methodsmentioning
confidence: 99%
“…Cell viability depends on the continuous supply of nutrients and oxygen, removal of waste products, low shear stress and the biocompatibility of materials. A number of characterization assays such as live/dead cell staining, drug testing, molecular profiling (e.g., FISH), as well as chemical, mechanical [90] and electrical stimulations are possible within microfluidic chips. These devices can also be coupled with on-chip tools for precise monitoring [91] and measurement of pH, oxygen level [92] and cell-secreted biomarkers [93], enabling a myriad of applications.…”
Section: Continuous-flow Microfluidic Spheroid Formation and Culturementioning
confidence: 99%
“…Inspired by the strategy of arrays of discrete microfabricated pillars (posts) of silicone elastomer to measure forces exerted by single cells [12, 13], we previously developed a technological process for fabricating high aspect ratio polydimethylsiloxane (PDMS) micropillars (300μm in height) with different diameters adapted to the characterization of the mechanical interactions between a growing multicellular tumour spheroid and its environment. The microdevices are made of 300 μm high cylindrical PDMS micropillars, arranged in a circular manner around the spheroid [14]. Using time-lapse video-microscopy, we demonstrated that pillar displacement induced by growing spheroids depends on pillar stiffness.…”
Section: Introductionmentioning
confidence: 99%